2012
DOI: 10.1186/1471-2180-12-166
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Mycobacterium bovis strains differ in their ability to modulate the proinflammatory activation phenotype of macrophages

Abstract: BackgroundTuberculosis, caused by Mycobacterium tuberculosis or Mycobacterium bovis, remains one of the leading infectious diseases worldwide. The ability of mycobacteria to rapidly grow in host macrophages is a factor contributing to enhanced virulence of the bacteria and disease progression. Bactericidal functions of phagocytes are strictly dependent on activation status of these cells, regulated by the infecting agent and cytokines. Pathogenic mycobacteria can survive the hostile environment of the phagosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 25 publications
2
25
0
1
Order By: Relevance
“…More precisely, cells from Beijing 1471 Mtb -infected C57BL/6 mice produced higher levels of IL-1β and IFNγ. In contrast, cells from MP287/03 Mbv -infected mice secreted comparatively lower levels of pro-inflammatory cytokines and higher levels of IL-10, which supports the notion that MP287/03 Mbv is a poor inducer of pro-inflammatory cytokines [38]. As observed for the composition of cellular infiltrates, the absence of P2X7R had different effects on the cytokine profiles induced by hypervirulent strains.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…More precisely, cells from Beijing 1471 Mtb -infected C57BL/6 mice produced higher levels of IL-1β and IFNγ. In contrast, cells from MP287/03 Mbv -infected mice secreted comparatively lower levels of pro-inflammatory cytokines and higher levels of IL-10, which supports the notion that MP287/03 Mbv is a poor inducer of pro-inflammatory cytokines [38]. As observed for the composition of cellular infiltrates, the absence of P2X7R had different effects on the cytokine profiles induced by hypervirulent strains.…”
Section: Resultssupporting
confidence: 75%
“…Thus, eATP induced the P2X7R-mediated killing of H37Rv Mtb bacilli and the P2X7R-mediated release of viable Beijing 1471 Mtb and MP287/03 Mbv bacilli. The resistance of these hypervirulent mycobacteria to intracellular killing has also been described following macrophage stimulation with IFNγ [37], [38] and can be attributed to the ability of pathogenic mycobacteria to block phagosome-lysosome fusion [57]. The moderate extent of tissue damage with consequently small amounts of eATP release and the susceptibility to eATP-induced intracellular killing explain, respectively, the lack of involvement or the protective role of P2X7R during the H37Rv Mtb infection [39], [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bone marrow-derived macrophages (BMDM) were obtained through the cultivation of bone marrow cells of C57BL/6 mice in Dulbecco's modified Eagle medium-nutrient mixture F-12 (DMEM/F12) complemented with 20% L929 cell-conditioned medium (as a source of macrophage colony-stimulating factor [M-CSF] to induce macrophage differentiation), as previously described (23). The cells were infected with the mycobacterial strains at a multiplicity of infection (MOI) of 1:1 bacterium/macrophage.…”
Section: Mycobacterial Isolates and Genotype Classificationmentioning
confidence: 99%
“…The properties of M2 macrophages are resolving/anti-inflammatory function, neuro/axonal-trophic support and scar-degrading capacities . Markers for M2 macrophages are arginase-1, Ym1, found in inflammatory zone 1 (FIZZ1), CD206, CD209, CD163, and mannose receptor (MR) and IL-1 receptor antagonist (IL-1Ra) ( Table 2) (Simmons and Seed, 1988;Ezekowitz et al, 1990;Law et al, 1993;Relloso et al, 2002;Menzies et al, 2010;Komori et al, 2011;Andrade et al, 2012;Rodriguez Guerrero et al, 2012;Varnum and Ikezu, 2012). Kigerl et al (2009) showed a comparatively smaller and transient M2 macrophage response in SCI, which probably explains the prolonged pro-inflammatory response, with detrimental effects on tissue viability if not terminated on time .…”
Section: Alternatively Activated Macrophages (M2)mentioning
confidence: 97%